2021
DOI: 10.13005/ojc/370506
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Utility of Some Schiff Bases and their Complexes with First Transition Series Metals: A Review

Abstract: Schiff based ligands and their complexes have emerged as potential drug candidates. Owing to their excellent chelating tendency, they easily coordinate with transition metals which have vacant orbitals. Transition metal complexes have several advantages because of their better acceptability and low toxicity in biological systems. These metals also serve as micronutrients and as co-factors of various metallo-enzymes which justifies the need of their designing and synthesis. Many modifications have been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…21,22 Schiff bases have applications in many elds, 23 e.g. pharmacology, 24,25 medicine, 26 catalysis, 27 dyes 28,29 and photoswitching materials. 30,31 The biological activity of these molecules can be enhanced by coordination with various metal ions, [32][33][34][35] due to their excellent chelating properties.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Schiff bases have applications in many elds, 23 e.g. pharmacology, 24,25 medicine, 26 catalysis, 27 dyes 28,29 and photoswitching materials. 30,31 The biological activity of these molecules can be enhanced by coordination with various metal ions, [32][33][34][35] due to their excellent chelating properties.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance is another major obstacle wwhich is linked to increased mortality rate associated with infectious diseases. This particular issue calls for discovery of novel drugs having effective mechanisms [ 81 ]. The ligands and the complexes were evaluated for their antibacterial activity against P. aeruginosa, C. jejuni, L. monocytogenes, B. subtilis, S. aureus, E. coli, S. pyogenes,C.…”
Section: Resultsmentioning
confidence: 99%
“…The MBC values of the complexes were either the same or two-four-fold higher than the initial MIC (Table 8 ). A previous study reported that inorganic based materials could dephosphorylate tyrosine precipitates on the peptide layer and the bacterial signal transduction is also influenced via phosphorylation of protein layer [ 81 ]. As compared to the free ligand, complexes exhibited better antibacterial activity which can be due to chelation, as reported previously [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…The modification that persists in the structure is replacement of the carbonyl group with the imine group (-N=CH-). SBs are the byproduct of the acid catalyzed condensation of 1° amines and carbonyl compounds [5][6][7].…”
Section: General Structure Of Schiff Basesmentioning
confidence: 99%